2022
DOI: 10.1002/prp2.910
|View full text |Cite
|
Sign up to set email alerts
|

Risk of genital and urinary tract infections associated with SGLT‐2 inhibitors as an add‐on therapy to metformin in patients with type 2 diabetes mellitus: A retrospective cohort study in Korea

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…One of the most acknowledged side effects when using SGLT-2i therapy is genitourinary infection [ 55 ]. Nevertheless, a recent Korean study demonstrated that genital and urinary tract infections appear to be two- to three-fold more frequent in females and patients over 60 years old [ 56 ], emphasizing the need for the rigorous monitoring of these categories.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most acknowledged side effects when using SGLT-2i therapy is genitourinary infection [ 55 ]. Nevertheless, a recent Korean study demonstrated that genital and urinary tract infections appear to be two- to three-fold more frequent in females and patients over 60 years old [ 56 ], emphasizing the need for the rigorous monitoring of these categories.…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous study using Korean claims data, the use of SGLT2 inhibitors significantly increased genital and urinary tract infections, and these side effects were reported to occur more commonly in older patients and in females. 7 Therefore, it is necessary to be cautious in prescribing drugs of the SGLT2 inhibitor class to elderly women and in cases with a history of previous genitourinary infection.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes itself is a well-known risk factor for infections as high blood glucose, compromised immune systems, and comorbid conditions can predispose patients to infectious disorders 9 11 . Safety signals have been detected thus far primarily with two major oral antidiabetic classes, DPP-4 inhibitors and SGLT-2 inhibitors, in terms of their potential to increase the risk of respiratory and urogenital infections, respectively 5 7 , 20 23 . To the best of our knowledge, this is the first study that defined the study patients as only those with advanced T2DM already on insulin treatment and investigated the effects of DPP-4 inhibitors and SGLT-2 inhibitors on infectious disease risks as compared to metformin effects in these patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…These patient populations are susceptible to adverse health outcomes due to life-long exposure to hypoglycemic therapy and the attributes of T2DM itself that typically progresses to various metabolic dysfunctions 4 . Recently, it has been speculated in a series of studies that certain glucose-lowering agents, particularly dipeptidyl peptidase-4 (DPP-4) inhibitors and sodium glucose cotransporter-2 (SGLT-2) inhibitors, might be associated with increased risk of infectious diseases 5 7 . Given that the prescription volume of the two antidiabetic classes is steadily on the rise 8 , a potential link between their use and infection risks, albeit still controversial, may well leave healthcare professionals worldwide uncertain about optimal glycemic control regimens for T2DM patients who are already predisposed to infections due to diabetes-associated impaired immune responses 9 11 .…”
Section: Introductionmentioning
confidence: 99%